HUBUNGAN AKTIVITAS FISIK, POLA MAKAN, JENIS KELAMIN, TEMAN SEBAYA DAN UANG SAKU DENGAN KEJADIAN GIZI LEBIH PADA ANAK DI SEKOLAH DASAR NEGERI 002 SEKUPANG KOTA BATAM TAHUN 2022 - Made Tantra Wirakesuma; Desy Desy; Okta Berliana Putri (Pusat Riset dan Inovasi Nasional, 2022)
Overnutrition is the excessive accumulation of fat in the body. Child overweight is also increasing, with one in five primary school age children in Indonesia being overweight. The prevalence of overweight in children reaches 5.4% in developing countries. Many factors influence over nutrition including dietary habit, physical activity, peers, and pocket money. This study aims to determine the relationship between physical activity, dietary habit, gender, peers and pocket money with the incidence of overnutrition in children at the 002 Sekupang State Elementary School, Batam City. This research is an analytic study with a cross sectional. Respondents in this study were 63 respondents with the sampling technique used was Probability Sampling with Stratified Random Sampling.statistical test chi- square showed that there was a relationship between physical activity (p = 0.001< 0.01), dietary habit (p = 0.000 < 0.01), peers (p = 0.005 < 0.01), pocket money (p = 0.004 < 0.01), and there is no gender relationship (p = 0.124) with the incidence of overnutrition due to the value (p value > 0.01). It is hoped that parents will be able to regulate a balanced dietary habit, balanced with good physical activity, and not give excess pocket money in order to overcome nutrition status problems in children.